TERAPI RELAKSASI NAFAS DALAM UNTUK PENATALAKSANAAN NYERI AKUT PASIEN CA UTERI - Ita Triatun Solikhah; Indri Heri Susanti; Dian Fitriani (Sekolah Tinggi Pariwisata Mataram, 2023)
As time goes by, uterine cavities and complaints of pain with high quality and longer duration increase. Such conditions make pain one of the symptoms most often felt by ca uteri patients and make it a top priority for nursing diagnoses that often appear in nursing care. An uncomfortable condition that comes from physical and psychological problems, ca uteri patients are expected to be able to control the pain. The purpose of this case study is to provide alternative interventions that can be performed for ca uteri patients non-pharmacologically. Deep breathing relaxation can reduce muscle tension, and anxiety to prevent increased pain stimulation, as an alternative to pain management. This research used a case study with a nursing care approach as a descriptive method. All ca uteri patients were included in the study population through simple random sampling method. One ca uteri patient participated in this study. The results of the study found that deep relaxation can reduce the discomfort scale of pain intensity and duration of pain so that patients can rest. It has been proven that deep breathing relaxation therapy can reduce pain by using it 10 times a day for three days, with a break every five times. The patient no longer complained of pain and showed a decrease in pain and anxiety